THE EFFECT OF COMPETENCE, TRANSPARENCY, ACCOUNTABILITY, AND PARTICIPATION ON VILLAGE GOVERNMENT PERFORMANCE - Tiara Kusuma Wardiyanti; Gideon Setyo Budiwitjaksono (Jurnal Proaksi, 2021)
This research takes relevant issues regarding competence, transparency, accountability community participation, and village government performance. This study aims to examine the effect of Competence, Transparency, Accountability, Participation on the Performance of the Panglungan Village Government, Wonosalam District, Jombang Regency. The method used is a quantitative method. The sampling technique used in this research is purposive sampling with certain criteria. This study uses primary data by collecting data using the questionnaire method by distributing questionnaires, then the Village Apparatus and the Panglungan Village Community fill out the questionnaire. The analysis technique in this study uses Partial Least Square (PLS) with WarpPLS 7.0 software. The Structural Equation Model (SEM) analysis method consists of two sub models, namely the measurement model or often called the outer model and the structural model or often called the inner model. Based on the test results, it can be concluded that competence has a positive effect on the performance of the Panglungan Village government. Transparency has a positive effect on the performance of the Panglungan Village government. Accountability does not have a positive effect on the performance of the Panglungan Village government. Participation has a positive effect on the performance of the Panglungan Village government. Keywords: Competence, Transparency, Accountability, Participation, Performance